KARYA PEMBANGUNGAN DI PASIR BARAT JAMBE, TANGERANG BANTEN - Yulfitri, Alivia (Jurnal Pengabdian Masyarakat AbdiMas, 2017)
AbstractUtilization of the Internet using a web browser, currently being media and learning resources that unlimited. Advancement of science and information technology has expanded the media to acquire knowledge and learning of students and teachers easily. Media teaching in schools is not just rely on the teacher as the sole source of information. Similarly, textbooks and the surrounding environment. Internet becomes a media of learning the most practical to complement all media and learning resources that already exist. In addition, through the internet provided a variety of information, learning resources, and books that some can be downloaded free of charge by students and teachers. It is very helpful learning in which the price of books had been more expensive. Current conditions, vocational students are not familiar in the use and utilization of the Internet in the learning process. Therefore, held training use of the Internet using a web browser at SMK, as a form of community service in college. The training given to students and teachers. The Internet application using a web browser application Internet Explorer and Firefox. The training discussed on the internet, web browser, benefits. how to setting, how to use the application as well as take advantage of search engine. The results achieved are expected students and teachers can utilize the internet using a web browser to obtain the information, science, knowledge and free books to support the learning process in schools. Keywords: internet, web browser, learning, information technologyÃ‚Â AbstrakPemanfaatan Internet menggunakan browser web, saat ini sedang media dan sumber belajar yang tak terbatas. Kemajuan ilmu pengetahuan dan teknologi informasi telah memperluas media untuk memperoleh pengetahuan dan pembelajaran siswa dan guru dengan mudah. Pengajaran media di sekolah tidak hanya mengandalkan guru sebagai satu-satunya sumber informasi. Begitu pula buku teks dan lingkungan sekitar. Internet menjadi media pembelajaran yang paling praktis untuk melengkapi semua media dan sumber belajar yang sudah ada. Selain itu, melalui internet disediakan beragam informasi, sumber belajar, dan buku yang beberapa dapat didownload secara gratis oleh siswa dan guru. Sangat membantu belajar dimana harga buku menjadi lebih mahal. Kondisi saat ini, siswa SMK tidak asing lagi dalam penggunaan dan pemanfaatan internet dalam proses pembelajaran. Oleh karena itu, diadakan penggunaan pelatihan internet dengan menggunakan browser web di SMK, sebagai bentuk pengabdian masyarakat di perguruan tinggi. Pelatihan diberikan kepada siswa dan guru. Aplikasi internet menggunakan aplikasi web browser Internet Explorer dan Firefox. Pelatihan dibahas di internet, web browser, tunjangan. Cara settingnya, cara menggunakan aplikasi sekaligus memanfaatkan mesin pencari. Hasil yang diraih diharapkan siswa dan guru dapat memanfaatkan internet menggunakan browser web untuk mendapatkan informasi, sains, pengetahuan dan buku gratis untuk menunjang proses pembelajaran di sekolah.Kata kunci: internet, browser web, pembelajaran, teknologi informas